A kind of cut-resistant ultra-high molecular weight polyethylene fiber and preparation method thereof

Through the combination of modified filler and ultra-high molecular weight polyethylene powder and the spray protective layer of graphene oxide, the lack of performance of traditional ultra-high molecular weight polyethylene fibers under the demand for extremely high cutting resistance is solved, and the cutting resistance and mechanical properties of the fiber are significantly improved.

CN119777017APending Publication Date: 2025-04-08JIUZHOU INTERSTELLAR TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411853194.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In certain specific application scenarios, especially in environments where extremely high cutting resistance is required, its performance has gradually become difficult to meet the requirements.

Method used

By mixing modified zirconium phosphate, modified nanomontmorillonite, modified glass microbeads and modified nanotitanium dioxide at a specific weight ratio, ball milling to form a modified filler, and mixing it with ultra-high molecular weight polyethylene powder and white oil, after spinning, cooling, extraction, drying and thermal drafting treatment, finally spraying graphene oxide on the fiber surface to form a protective film, and cutting-resistant ultra-high molecular weight polyethylene fibers are prepared.

Benefits of technology

It significantly improves the cutting resistance, mechanical properties and wear resistance of the fiber, enhances the compatibility and interface bonding force between the fiber and the polymer matrix, and extends the service life of the fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005191100100000121
    Figure BDA0005191100100000121
Patent Text Reader

Abstract

The invention relates to the technical field of polymer fibers, and in particular to a cut-resistant ultra-high molecular weight polyethylene fiber and a preparation method thereof. The invention uses trihydroxymethylaminomethane to perform surface modification on alpha-zirconium phosphate, and then introduces vinyltriethoxysilane to form chemical bonding, thereby enhancing the compatibility of zirconium phosphate with a polymer matrix. The modified nano-montmorillonite, modified glass microbeads and modified nano-titanium dioxide in the invention are all prepared after surface modification with a silane coupling agent, aiming to improve their dispersibility and interface bonding with polymers. One end of the silane coupling agent can react with a hydroxyl group on the surface of an inorganic material, and the other end can chemically bond with a polymer chain, thereby forming a bridge to enhance the interaction between the two. Moreover, the modified nano-montmorillonite, glass microbeads and nano-titanium dioxide can be more effectively dispersed in a polymer matrix, thereby significantly improving the stiffness, strength and wear resistance of the fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer fibers, and in particular to a cut-resistant ultra-high molecular weight polyethylene fiber and a preparation method thereof. Background Art

[0002] Ultra-high molecular weight polyethylene fibers have been widely used in safety protection, military equipment, sporting goods and many industrial fields due to their excellent mechanical properties, wear resistance and chemical corrosion resistance. However, with the development of science and technology and the continuous improvement of application needs, the performance of traditional ultra-high molecular weight polyethylene fibers in certain specific application scenarios, such as environments that require extremely high cut resistance, has gradually failed to meet the requirements. The preparation process of traditional ultra-high molecular weight polyethylene fibers mainly relies on melt spinning or gel spinning technology. Although these technologies can produce fibers with high strength and high modulus, their cut resistance still needs to be improved.

[0003] In order to improve the cut resistance of ultra-high molecular weight polyethylene fibers, a common strategy is to improve the mechanical properties and cut resistance of the fibers by adding reinforcing materials, such as nanoparticles, fibrous reinforcements, etc. However, these reinforcing materials often have problems such as poor dispersibility and poor compatibility with the polymer matrix, which leads to uneven distribution in the fibers and difficulty in fully exerting their reinforcing effects. In addition, the surface of traditional ultra-high molecular weight polyethylene fibers is relatively smooth and lacks sufficient friction and anti-cutting protective layers. When cut by sharp objects, cracks are easily formed on the fiber surface and expand rapidly, resulting in the destruction of the overall fiber structure. Therefore, how to form a protective layer with excellent cut resistance on the fiber surface through surface modification technology is also the key to improving the cut resistance of ultra-high molecular weight polyethylene fibers. Summary of the invention

[0004] Technical issues solved

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a cut-resistant ultra-high molecular weight polyethylene fiber and a preparation method thereof, which can effectively solve the problems of poor mechanical properties and cut resistance of the ultra-high molecular weight polyethylene fiber in the prior art.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A method for preparing cut-resistant ultra-high molecular weight polyethylene fiber, the preparation method comprising:

[0009] S1, mixing modified zirconium phosphate, modified nano-montmorillonite, modified glass microbeads and modified nano-titanium dioxide in a weight ratio of 2:1:1:2 and pouring into a ball mill, and the mixture obtained after ball milling for 10 minutes is recorded as modified filler;

[0010] S2, after 0.5-1 parts by weight of modified filler and 10 parts by weight of white oil are mixed and dispersed, the obtained result is recorded as modified component, and after 20 parts by weight of ultra-high molecular weight polyethylene powder and 180 parts by weight of white oil are mixed and treated, the obtained result is recorded as spinning solution;

[0011] S3, pouring the modified component into the spinning solution, stirring evenly, and then extruding through a twin-screw spinning machine to form fiber precursors, and obtaining ultra-high molecular weight polyethylene fibers after cooling, extraction, drying and multi-stage heat drawing treatment;

[0012] S4. Spray the graphene oxide dispersion on the surface of the ultra-high molecular weight polyethylene fiber at a spray bath ratio of 1:50, place it in an oven at 60° C. and dry it for 3-5 hours to obtain the cut-resistant ultra-high molecular weight polyethylene fiber.

[0013] Furthermore, the preparation steps of the modified zirconium phosphate in S1 are:

[0014] Step 1, dispersing 2g of α-zirconium phosphate in 100mL of deionized water, and the result after uniform dispersion is recorded as α-zirconium phosphate dispersion, dissolving 1g of tris(hydroxymethyl)aminomethane in 20mL of deionized water, and the result after dispersion and dissolution is recorded as tris(hydroxymethyl)aminomethane solution;

[0015] Step 2, dripping the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 1 drop / s, followed by ultrasonic treatment at a frequency of 40 kHz for 20 min, washing the precipitate after centrifugation with deionized water for 3 times, and finally drying it in a freeze dryer for 48 h, and the obtained precipitate is recorded as pretreated α-zirconium phosphate;

[0016] Step 3: Add 2 g of pretreated α-zirconium phosphate, 200 mL of anhydrous ethanol, 20 mL of deionized water and 2 mL of vinyltriethoxysilane into a flask, heat and reflux at 80° C. for 4 h, wash the resulting product and dry it in a freeze dryer for 48 h to obtain modified zirconium phosphate.

[0017] Furthermore, the specific operation of uniform dispersion in step 1 is stirring at a stirring speed of 300 r / min for 30 minutes, the specific operation of dispersion and dissolution in step 1 is stirring at a stirring speed of 500 r / min for 10 minutes, the specific operation of centrifugal treatment in step 2 is centrifugation at a speed of 6000 r / min for 5 minutes, and the specific operation of washing treatment in step 3 is washing twice with anhydrous ethanol and then washing once with deionized water.

[0018] Furthermore, the preparation method of the modified nano-montmorillonite in S1 is:

[0019] Weigh 10g of nano-montmorillonite and 40g of anhydrous ethanol and mix them. After ultrasonic treatment at a frequency of 30kHz for 30min, add 0.5g of silane coupling agent KH-570, and magnetically stir at a stirring speed of 300r / min in a constant temperature water bath at 85°C until the anhydrous ethanol is completely evaporated. Continue stirring for 30min and then place in an oven at 65°C to dry for 6h. Grind through a 200-mesh sieve to obtain the modified nano-montmorillonite.

[0020] Furthermore, the preparation method of the modified glass microspheres in S1 is:

[0021] Pour 0.8g of silane coupling agent KH-560 into 200mL of acetone solution, stir at a stirring speed of 300r / min for 10min, then add 12g of glass beads with an average particle size of 10μm, stir at a stirring speed of 600r / min until the acetone evaporates, and place in an oven at 80°C to dry for 6h to obtain modified glass beads.

[0022] Furthermore, the preparation method of the modified nano titanium dioxide in S1 is:

[0023] First, add 0.3g of silane coupling agent KH-570 into 5mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 26kHz for 10min to obtain a coupling agent solution; then disperse 5g of nano-titanium dioxide in 300mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 28kHz for 30min, then add 5mL of coupling agent solution dropwise and stir at a stirring speed of 200r / min for 6h in a 70°C water bath to react, finally centrifuge at a speed of 10000r / min for 5min, and then dry the precipitate in an oven at 80°C for 4h to obtain modified nano-titanium dioxide.

[0024] Furthermore, the specific operation of mixing and dispersing in S2 is first stirring at a stirring speed of 800 r / min for 30 min, and then ultrasonically dispersing at a frequency of 40 kHz for 30 min. The specific operation of mixing treatment in S2 is stirring at a stirring speed of 500 r / min for 30 min. The specific operation of stirring evenly in S3 is stirring at a stirring speed of 300 r / min for 10 min.

[0025] Furthermore, the specific operations of cooling, extraction, drying and multi-stage hot stretching treatment in S3 are:

[0026] The fiber precursors in S3 are first cooled in a cooling water tank and then pre-stretched by 2-4 times, then ultrasonically extracted in an extraction tank containing a dichloromethane extractant for 10-20 minutes, then placed in a drying oven for 10-25 minutes to evaporate the extractant through hot air drying, and finally subjected to multiple heat stretching on a seven-roller stretching machine, with a stretching multiple of 25-50 times and a stretching temperature of 130-140°C.

[0027] Furthermore, the preparation method of the graphene oxide dispersion in S3 is:

[0028] 5-6 g of graphene oxide is dispersed in methanol and subjected to ultrasonic treatment at a frequency of 30 kHz for 1 hour to obtain a graphene oxide dispersion.

[0029] A cut-resistant ultra-high molecular weight polyethylene fiber is prepared by a method for preparing the cut-resistant ultra-high molecular weight polyethylene fiber.

[0030] Beneficial Effects

[0031] The present invention provides a cut-resistant ultra-high molecular weight polyethylene fiber and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The present invention modifies the surface of α-zirconium phosphate by using trihydroxymethylaminomethane, and then introduces vinyltriethoxysilane to form a chemical bond, which can enhance the compatibility of zirconium phosphate with a polymer matrix, and can not only improve the dispersibility of zirconium phosphate, but also increase its interfacial bonding force with ultra-high molecular weight polyethylene, thereby improving the overall strength and toughness of the fiber; secondly, the modified zirconium phosphate can effectively improve the heat resistance and flame retardancy of the fiber, while enhancing the mechanical properties of the fiber, making it tougher when facing external forces such as cutting.

[0033] 2. The modified nano-montmorillonite, modified glass microbeads and modified nano-titanium dioxide in the present invention are all obtained after surface modification with a silane coupling agent, aiming to improve their dispersibility and interfacial bonding with the polymer. One end of the silane coupling agent can react with the hydroxyl group on the surface of the inorganic material, and the other end can chemically bond with the polymer chain, thereby forming a bridge to enhance the interaction between the two. Moreover, the modified nano-montmorillonite, glass microbeads and nano-titanium dioxide can be more effectively dispersed in the polymer matrix, reduce agglomeration, improve the uniformity and overall performance of the fiber material, and significantly improve the stiffness, strength and wear resistance of the fiber.

[0034] 3. In the present invention, graphene oxide is a high-performance two-dimensional material with excellent mechanical properties and barrier properties. It is evenly attached to the fiber surface by spraying to form a protective film. The introduction of graphene oxide can significantly improve the cut resistance and wear resistance of the fiber. At the same time, its good barrier properties can effectively prevent the external environment from eroding the fiber and extend the service life of the fiber. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The present invention will be further described below in conjunction with the embodiments.

[0037] Example 1

[0038] A method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber in this embodiment is as follows:

[0039] S1, mixing modified zirconium phosphate, modified nano-montmorillonite, modified glass microbeads and modified nano-titanium dioxide in a weight ratio of 2:1:1:2 and pouring into a ball mill, and the mixture obtained after ball milling for 10 minutes is recorded as modified filler;

[0040] Wherein, the preparation steps of the modified zirconium phosphate in S1 are:

[0041] Step 1, dispersing 2g of α-zirconium phosphate in 100mL of deionized water, stirring at a stirring speed of 300r / min for 30min, the result is recorded as α-zirconium phosphate dispersion, dissolving 1g of tris(hydroxymethyl)aminomethane in 20mL of deionized water, stirring at a stirring speed of 500r / min for 10min, the result is recorded as tris(hydroxymethyl)aminomethane solution;

[0042] Step 2, dripping the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 1 drop / s, then ultrasonically treating at a frequency of 40 kHz for 20 minutes, centrifuging at a speed of 6000 r / min for 5 minutes, washing the precipitate with deionized water three times, and finally drying it in a freeze dryer for 48 hours, and the obtained result is recorded as pretreated α-zirconium phosphate;

[0043] Step 3: Add 2 g of pretreated α-zirconium phosphate, 200 mL of anhydrous ethanol, 20 mL of deionized water and 2 mL of vinyltriethoxysilane into a flask, heat and reflux at 80°C for 4 h, wash the resulting product twice with anhydrous ethanol and once with deionized water, and dry it in a freeze dryer for 48 h to obtain modified zirconium phosphate.

[0044] The preparation method of modified nano-montmorillonite in S1 is:

[0045] Weigh 10g of nano-montmorillonite and 40g of anhydrous ethanol and mix them. After ultrasonic treatment at a frequency of 30kHz for 30min, add 0.5g of silane coupling agent KH-570, and magnetically stir at a stirring speed of 300r / min in a constant temperature water bath at 85°C until the anhydrous ethanol is completely evaporated. Continue stirring for 30min and then place in an oven at 65°C to dry for 6h. Grind through a 200-mesh sieve to obtain the modified nano-montmorillonite.

[0046] The preparation method of the modified glass microspheres in S1 is:

[0047] Pour 0.8g of silane coupling agent KH-560 into 200mL of acetone solution, stir at a stirring speed of 300r / min for 10min, then add 12g of glass beads with an average particle size of 10μm, stir at a stirring speed of 600r / min until the acetone evaporates, and place in an oven at 80°C to dry for 6h to obtain modified glass beads.

[0048] The preparation method of modified nano titanium dioxide in S1 is:

[0049] First, add 0.3g of silane coupling agent KH-570 into 5mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 26kHz for 10min to obtain a coupling agent solution; then disperse 5g of nano-titanium dioxide in 300mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 28kHz for 30min, then add 5mL of coupling agent solution dropwise and stir at a stirring speed of 200r / min for 6h in a 70°C water bath to react, finally centrifuge at a speed of 10000r / min for 5min, and then dry the precipitate in an oven at 80°C for 4h to obtain modified nano-titanium dioxide.

[0050] S2, 0.5 parts by weight of modified filler and 10 parts by weight of white oil are mixed and dispersed, and the obtained result is recorded as modified component, and 20 parts by weight of ultra-high molecular weight polyethylene powder and 180 parts by weight of white oil are mixed and treated, and the obtained result is recorded as spinning solution;

[0051] The specific operation of mixing and dispersing in S2 is to first stir at a stirring speed of 800 r / min for 30 min, and then ultrasonically disperse at a frequency of 40 kHz for 30 min. The specific operation of mixing treatment in S2 is to stir at a stirring speed of 500 r / min for 30 min.

[0052] S3, pouring the modified component into the spinning solution and stirring at a stirring speed of 300r / min for 10min, extruding through a twin-screw spinning machine to form fiber precursors, and obtaining ultra-high molecular weight polyethylene fibers after cooling, extraction, drying and multi-stage heat drawing treatment;

[0053] The specific operations of cooling, extraction, drying and multi-stage hot stretching treatment in S3 are as follows:

[0054] The fiber precursors in S3 were first cooled in a cooling water tank and then pre-stretched twice, then ultrasonically extracted in an extraction tank containing a dichloromethane extractant for 10 minutes, then placed in a drying oven for 10 minutes to evaporate the extractant through hot air drying, and finally subjected to multiple heat stretching on a seven-roller stretching machine with a stretching multiple of 25 times and a stretching temperature of 130°C.

[0055] The preparation method of the graphene oxide dispersion in S3 is: 5 g of graphene oxide is dispersed in methanol, and the obtained graphene oxide dispersion is subjected to ultrasonic treatment at a frequency of 30 kHz for 1 hour.

[0056] S4. Spray the graphene oxide dispersion on the surface of the ultra-high molecular weight polyethylene fiber at a spray bath ratio of 1:50, and dry it in an oven at 60° C. for 3 hours to obtain the cut-resistant ultra-high molecular weight polyethylene fiber.

[0057] A cut-resistant ultra-high molecular weight polyethylene fiber is prepared by a method for preparing the cut-resistant ultra-high molecular weight polyethylene fiber.

[0058] Example 2

[0059] A method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber in this embodiment is as follows:

[0060] S1, mixing modified zirconium phosphate, modified nano-montmorillonite, modified glass microbeads and modified nano-titanium dioxide in a weight ratio of 2:1:1:2 and pouring into a ball mill, and the mixture obtained after ball milling for 10 minutes is recorded as modified filler;

[0061] Wherein, the preparation steps of the modified zirconium phosphate in S1 are:

[0062] Step 1, dispersing 2g of α-zirconium phosphate in 100mL of deionized water, stirring at a stirring speed of 300r / min for 30min, the result is recorded as α-zirconium phosphate dispersion, dissolving 1g of tris(hydroxymethyl)aminomethane in 20mL of deionized water, stirring at a stirring speed of 500r / min for 10min, the result is recorded as tris(hydroxymethyl)aminomethane solution;

[0063] Step 2, dripping the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 1 drop / s, then ultrasonically treating at a frequency of 40 kHz for 20 minutes, centrifuging at a speed of 6000 r / min for 5 minutes, washing the precipitate with deionized water three times, and finally drying it in a freeze dryer for 48 hours, and the obtained result is recorded as pretreated α-zirconium phosphate;

[0064] Step 3: Add 2 g of pretreated α-zirconium phosphate, 200 mL of anhydrous ethanol, 20 mL of deionized water and 2 mL of vinyltriethoxysilane into a flask, heat and reflux at 80°C for 4 h, wash the resulting product twice with anhydrous ethanol and once with deionized water, and dry it in a freeze dryer for 48 h to obtain modified zirconium phosphate.

[0065] The preparation method of modified nano-montmorillonite in S1 is:

[0066] Weigh 10g of nano-montmorillonite and 40g of anhydrous ethanol and mix them. After ultrasonic treatment at a frequency of 30kHz for 30min, add 0.5g of silane coupling agent KH-570, and magnetically stir at a stirring speed of 300r / min in a constant temperature water bath at 85°C until the anhydrous ethanol is completely evaporated. Continue stirring for 30min and then place in an oven at 65°C to dry for 6h. Grind through a 200-mesh sieve to obtain the modified nano-montmorillonite.

[0067] The preparation method of the modified glass microspheres in S1 is:

[0068] Pour 0.8g of silane coupling agent KH-560 into 200mL of acetone solution, stir at a stirring speed of 300r / min for 10min, then add 12g of glass beads with an average particle size of 10μm, stir at a stirring speed of 600r / min until the acetone evaporates, and place in an oven at 80°C to dry for 6h to obtain modified glass beads.

[0069] The preparation method of modified nano titanium dioxide in S1 is:

[0070] First, add 0.3g of silane coupling agent KH-570 into 5mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 26kHz for 10min to obtain a coupling agent solution; then disperse 5g of nano-titanium dioxide in 300mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 28kHz for 30min, then add 5mL of coupling agent solution dropwise and stir at a stirring speed of 200r / min for 6h in a 70°C water bath to react, finally centrifuge at a speed of 10000r / min for 5min, and then dry the precipitate in an oven at 80°C for 4h to obtain modified nano-titanium dioxide.

[0071] S2, after 1 part by weight of modified filler and 10 parts by weight of white oil are mixed and dispersed, the obtained result is recorded as modified component, and after 20 parts by weight of ultra-high molecular weight polyethylene powder and 180 parts by weight of white oil are mixed and treated, the obtained result is recorded as spinning solution;

[0072] The specific operation of mixing and dispersing in S2 is to first stir at a stirring speed of 800 r / min for 30 min, and then ultrasonically disperse at a frequency of 40 kHz for 30 min. The specific operation of mixing treatment in S2 is to stir at a stirring speed of 500 r / min for 30 min.

[0073] S3, pouring the modified component into the spinning solution and stirring at a stirring speed of 300r / min for 10min, extruding through a twin-screw spinning machine to form fiber precursors, and obtaining ultra-high molecular weight polyethylene fibers after cooling, extraction, drying and multi-stage heat drawing treatment;

[0074] The specific operations of cooling, extraction, drying and multi-stage hot stretching treatment in S3 are as follows:

[0075] The fiber precursors in S3 were first cooled in a cooling water tank and then pre-stretched 4 times, followed by ultrasonic extraction in an extraction tank containing dichloromethane extractant for 20 minutes, and then placed in a drying oven for 25 minutes to evaporate the extractant through hot air drying, and finally passed through a seven-roller drawing machine for multiple heat stretching with a stretching multiple of 50 times and a stretching temperature of 140°C.

[0076] The preparation method of the graphene oxide dispersion in S3 is: 6 g of graphene oxide is dispersed in methanol, and the obtained graphene oxide dispersion is subjected to ultrasonic treatment at a frequency of 30 kHz for 1 hour.

[0077] S4. Spray the graphene oxide dispersion on the surface of the ultra-high molecular weight polyethylene fiber at a spray bath ratio of 1:50, place it in an oven at 60° C. and dry it for 5 hours to obtain the cut-resistant ultra-high molecular weight polyethylene fiber.

[0078] A cut-resistant ultra-high molecular weight polyethylene fiber is prepared by a method for preparing the cut-resistant ultra-high molecular weight polyethylene fiber.

[0079] Example 3

[0080] A method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber in this embodiment is as follows:

[0081] S1, mixing modified zirconium phosphate, modified nano-montmorillonite, modified glass microbeads and modified nano-titanium dioxide in a weight ratio of 2:1:1:2 and pouring into a ball mill, and the mixture obtained after ball milling for 10 minutes is recorded as modified filler;

[0082] Wherein, the preparation steps of the modified zirconium phosphate in S1 are:

[0083] Step 1, dispersing 2g of α-zirconium phosphate in 100mL of deionized water, stirring at a stirring speed of 300r / min for 30min, the result is recorded as α-zirconium phosphate dispersion, dissolving 1g of tris(hydroxymethyl)aminomethane in 20mL of deionized water, stirring at a stirring speed of 500r / min for 10min, the result is recorded as tris(hydroxymethyl)aminomethane solution;

[0084] Step 2, dripping the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 1 drop / s, then ultrasonically treating at a frequency of 40 kHz for 20 minutes, centrifuging at a speed of 6000 r / min for 5 minutes, washing the precipitate with deionized water three times, and finally drying it in a freeze dryer for 48 hours, and the obtained result is recorded as pretreated α-zirconium phosphate;

[0085] Step 3: Add 2 g of pretreated α-zirconium phosphate, 200 mL of anhydrous ethanol, 20 mL of deionized water and 2 mL of vinyltriethoxysilane into a flask, heat and reflux at 80°C for 4 h, wash the resulting product twice with anhydrous ethanol and once with deionized water, and dry it in a freeze dryer for 48 h to obtain modified zirconium phosphate.

[0086] The preparation method of modified nano-montmorillonite in S1 is:

[0087] Weigh 10g of nano-montmorillonite and 40g of anhydrous ethanol and mix them. After ultrasonic treatment at a frequency of 30kHz for 30min, add 0.5g of silane coupling agent KH-570, and magnetically stir at a stirring speed of 300r / min in a constant temperature water bath at 85°C until the anhydrous ethanol is completely evaporated. Continue stirring for 30min and then place in an oven at 65°C to dry for 6h. Grind through a 200-mesh sieve to obtain the modified nano-montmorillonite.

[0088] The preparation method of the modified glass microspheres in S1 is:

[0089] Pour 0.8g of silane coupling agent KH-560 into 200mL of acetone solution, stir at a stirring speed of 300r / min for 10min, then add 12g of glass beads with an average particle size of 10μm, stir at a stirring speed of 600r / min until the acetone evaporates, and place in an oven at 80°C to dry for 6h to obtain modified glass beads.

[0090] The preparation method of modified nano titanium dioxide in S1 is:

[0091] First, add 0.3g of silane coupling agent KH-570 into 5mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 26kHz for 10min to obtain a coupling agent solution; then disperse 5g of nano-titanium dioxide in 300mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 28kHz for 30min, then add 5mL of coupling agent solution dropwise and stir at a stirring speed of 200r / min for 6h in a 70°C water bath to react, finally centrifuge at a speed of 10000r / min for 5min, and then dry the precipitate in an oven at 80°C for 4h to obtain modified nano-titanium dioxide.

[0092] S2, after 0.8 parts by weight of modified filler and 10 parts by weight of white oil are mixed and dispersed, the obtained result is recorded as modified component, and after 20 parts by weight of ultra-high molecular weight polyethylene powder and 180 parts by weight of white oil are mixed and treated, the obtained result is recorded as spinning solution;

[0093] The specific operation of mixing and dispersing in S2 is to first stir at a stirring speed of 800 r / min for 30 min, and then ultrasonically disperse at a frequency of 40 kHz for 30 min. The specific operation of mixing treatment in S2 is to stir at a stirring speed of 500 r / min for 30 min.

[0094] S3, pouring the modified component into the spinning solution and stirring at a stirring speed of 300r / min for 10min, extruding through a twin-screw spinning machine to form fiber precursors, and obtaining ultra-high molecular weight polyethylene fibers after cooling, extraction, drying and multi-stage heat drawing treatment;

[0095] The specific operations of cooling, extraction, drying and multi-stage hot stretching treatment in S3 are as follows:

[0096] The fiber precursors in S3 were first cooled in a cooling water tank and then pre-stretched 3 times, followed by 15 minutes of ultrasonic extraction in an extraction tank containing a dichloromethane extractant, and then placed in a drying oven for 18 minutes to evaporate the extractant through hot air drying, and finally passed through a seven-roller drawing machine for multiple heat stretching with a stretching multiple of 38 times and a stretching temperature of 135°C.

[0097] The preparation method of the graphene oxide dispersion in S3 is: 6 g of graphene oxide is dispersed in methanol, and the obtained graphene oxide dispersion is subjected to ultrasonic treatment at a frequency of 30 kHz for 1 hour.

[0098] S4. Spray the graphene oxide dispersion on the surface of the ultra-high molecular weight polyethylene fiber at a spray bath ratio of 1:50, place it in an oven at 60° C. and dry it for 4 hours to obtain the cut-resistant ultra-high molecular weight polyethylene fiber.

[0099] A cut-resistant ultra-high molecular weight polyethylene fiber is prepared by a method for preparing the cut-resistant ultra-high molecular weight polyethylene fiber.

[0100] Comparative Example 1

[0101] The cut-resistant ultra-high molecular weight polyethylene fiber and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the modified filler in Example 1 is replaced by the modified zirconium phosphate in Example 1.

[0102] Comparative Example 2

[0103] The cut-resistant ultra-high molecular weight polyethylene fiber and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the modified filler in Example 1 is replaced by the modified nano-montmorillonite in Example 1.

[0104] Comparative Example 3

[0105] The cut-resistant ultra-high molecular weight polyethylene fiber and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified filler in Example 1 is replaced by the modified glass microbeads in Example 1.

[0106] Comparative Example 4

[0107] The cut-resistant ultra-high molecular weight polyethylene fiber and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 4, the modified filler in Example 1 is replaced by the modified nano titanium dioxide in Example 1.

[0108] Performance Testing

[0109] The cut-resistant ultra-high molecular weight polyethylene fibers prepared in Examples 1-3 and Comparative Examples 1-4 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively. Then, the performances of Examples 1-3 and Comparative Examples 1-4 are tested. The specific testing methods and test items are as follows:

[0110] 1. The breaking strength, breaking elongation and elastic modulus of Examples 1-3 and Comparative Examples 1-4 were tested with reference to the standard of GB / 19997-1988, and the obtained data are recorded in the following table;

[0111] 2. The tensile strength of the single filaments of Examples 1-3 and Comparative Examples 1-4 was tested with reference to the standard of GB / 19975-2005, and the obtained data are recorded in the following table;

[0112]

[0113] It can be seen from the data in the above table that the breaking strength, breaking elongation, elastic modulus and single-filament tensile strength of the cut-resistant ultra-high molecular weight polyethylene fibers in Examples 1-3 are higher than those in Comparative Examples 1-4, indicating that the cut-resistant ultra-high molecular weight polyethylene fibers in Examples 1-3 have excellent mechanical properties and thus have better cut resistance.

[0114] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0115] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing cut-resistant ultra-high molecular weight polyethylene fiber, characterized in that: The preparation method is: S1, mixing modified zirconium phosphate, modified nano-montmorillonite, modified glass microbeads and modified nano-titanium dioxide in a weight ratio of 2:1:1:2 and pouring into a ball mill, and the mixture obtained after ball milling for 10 minutes is recorded as modified filler; S2, after 0.5-1 parts by weight of modified filler and 10 parts by weight of white oil are mixed and dispersed, the obtained result is recorded as modified component, and after 20 parts by weight of ultra-high molecular weight polyethylene powder and 180 parts by weight of white oil are mixed and treated, the obtained result is recorded as spinning solution; S3, pouring the modified component into the spinning solution, stirring evenly, and then extruding through a twin-screw spinning machine to form fiber precursors, and obtaining ultra-high molecular weight polyethylene fibers after cooling, extraction, drying and multi-stage heat drawing treatment; S4. Spray the graphene oxide dispersion on the surface of the ultra-high molecular weight polyethylene fiber at a spray bath ratio of 1:50, place it in an oven at 60° C. and dry it for 3-5 hours to obtain the cut-resistant ultra-high molecular weight polyethylene fiber.

2. The method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation steps of the modified zirconium phosphate in S1 are: Step 1, dispersing 2g of α-zirconium phosphate in 100mL of deionized water, and the result after uniform dispersion is recorded as α-zirconium phosphate dispersion, dissolving 1g of tris(hydroxymethyl)aminomethane in 20mL of deionized water, and the result after dispersion and dissolution is recorded as tris(hydroxymethyl)aminomethane solution; Step 2, dripping the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 1 drop / s, followed by ultrasonic treatment at a frequency of 40 kHz for 20 min, washing the precipitate after centrifugation with deionized water for 3 times, and finally drying it in a freeze dryer for 48 h, and the obtained precipitate is recorded as pretreated α-zirconium phosphate; Step 3: Add 2 g of pretreated α-zirconium phosphate, 200 mL of anhydrous ethanol, 20 mL of deionized water and 2 mL of vinyltriethoxysilane into a flask, heat and reflux at 80° C. for 4 h, wash the resulting product and dry it in a freeze dryer for 48 h to obtain modified zirconium phosphate.

3. The method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber according to claim 2, characterized in that: The specific operation of uniform dispersion in step 1 is stirring at a stirring speed of 300 r / min for 30 minutes, the specific operation of dispersion and dissolution in step 1 is stirring at a stirring speed of 500 r / min for 10 minutes, the specific operation of centrifugal treatment in step 2 is centrifugation at a speed of 6000 r / min for 5 minutes, and the specific operation of washing treatment in step 3 is washing twice with anhydrous ethanol and then washing once with deionized water.

4. The method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation method of modified nano-montmorillonite in S1 is: Weigh 10g of nano-montmorillonite and 40g of anhydrous ethanol and mix them. After ultrasonic treatment at a frequency of 30kHz for 30min, add 0.5g of silane coupling agent KH-570, and magnetically stir at a stirring speed of 300r / min in a constant temperature water bath at 85°C until the anhydrous ethanol is completely evaporated. Continue stirring for 30min and then place in an oven at 65°C to dry for 6h. Grind through a 200-mesh sieve to obtain the modified nano-montmorillonite.

5. The method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation method of the modified glass microspheres in S1 is: Pour 0.8g of silane coupling agent KH-560 into 200mL of acetone solution, stir at a stirring speed of 300r / min for 10min, then add 12g of glass beads with an average particle size of 10μm, stir at a stirring speed of 600r / min until the acetone evaporates, and place in an oven at 80°C to dry for 6h to obtain modified glass beads.

6. The method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation method of modified nano titanium dioxide in S1 is: First, add 0.3g of silane coupling agent KH-570 into 5mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 26kHz for 10min to obtain a coupling agent solution; then disperse 5g of nano-titanium dioxide in 300mL of anhydrous ethanol and ultrasonically disperse it at a frequency of 28kHz for 30min, then add 5mL of coupling agent solution dropwise and stir at a stirring speed of 200r / min for 6h in a 70°C water bath to react, finally centrifuge at a speed of 10000r / min for 5min, and then dry the precipitate in an oven at 80°C for 4h to obtain modified nano-titanium dioxide.

7. The method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The specific operation of mixing and dispersing in S2 is to first stir at a stirring speed of 800 r / min for 30 min, and then ultrasonically disperse at a frequency of 40 kHz for 30 min. The specific operation of mixing treatment in S2 is to stir at a stirring speed of 500 r / min for 30 min. The specific operation of stirring evenly in S3 is to stir at a stirring speed of 300 r / min for 10 min.

8. The method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The specific operations of cooling, extraction, drying and multi-stage hot stretching treatment in S3 are: The fiber precursors in S3 are first cooled in a cooling water tank and then pre-stretched by 2-4 times, then ultrasonically extracted in an extraction tank containing a dichloromethane extractant for 10-20 minutes, then placed in a drying oven for 10-25 minutes to evaporate the extractant through hot air drying, and finally subjected to multiple heat stretching on a seven-roller stretching machine, with a stretching multiple of 25-50 times and a stretching temperature of 130-140°C.

9. The method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation method of the graphene oxide dispersion in S3 is: 5-6 g of graphene oxide is dispersed in methanol and subjected to ultrasonic treatment at a frequency of 30 kHz for 1 hour to obtain a graphene oxide dispersion.

10. A cut-resistant ultra-high molecular weight polyethylene fiber, characterized in that: The fiber is prepared by the method for preparing a cut-resistant ultra-high molecular weight polyethylene fiber as described in any one of claims 1 to 9.